Trend-following trading strategies in commodity futures: A re-examination - Szakmary, Andrew C.; Shen, Qian; Sharma, Subhash C. (Journal of Banking & Finance, 2010)
This paper examines the performance of trend-following trading strategies in commodity futures markets using a monthly dataset spanning 48years and 28 markets. We find that all parameterizations of the dual moving average crossover and channel strategies that we implement yield positive mean excess returns net of transactions costs in at least 22 of the 28 markets. When we pool our results across markets, we show that all of the trading rules earn hugely significant positive returns that prevail over most subperiods of the data as well. These results are robust with respect to the set of commodities the trading rules are implemented with, distributional assumptions, data-mining adjustments and transactions costs, and help resolve divergent evidence in the extant literature regarding the performance of momentum and pure trend-following strategies that is otherwise difficult to explain.